PREVALENCE OF DEPRESSION AMONG MEDICAL STUDENTS IN SAUDI ARABIA (CAHIERS MAGELLANES-NS, 2024)
Background: Depression is a common mental condition that manifests as sadness, a lack of interest or enjoyment, a sense of guilt or low self-worth, interrupted sleep or food, fatigue, and difficulty concentrating. According to the World Health Organization, mental health is a crucial component of health. This study aimed to determine the prevalence of depression among medical students during their clinical years in SA. Methods: This is a cross-sectional study conducted in Saudi Arabia, using questionnaire, data was collected from adult male and female medical students in their clinical years from the kingdom of Saudi Arabia from August to November 2023 in Saudi medical college. The data was analyzed with the help of Microsoft excel and SPSS. Results: As regard the prevalence of depression among medical students, there was 85% out of 740 participants exhibited some level of depressive symptoms. The largest group, representing 31.4% of the sample, falls under the "mild depression" category. Furthermore, 25.6% of the students were experiencing moderate to severe levels of depression and 28% reported moderate depression. Moreover, no statistically significant relation was found between gender and depressive symptoms (p value =0.421). Conclusion: the study revealed that a striking 85% of participants reporting some level of depression. These findings align with global research indicating that medical students are at an increased risk for mental health issues, often exacerbated by the rigorous demands of their education. Notably, despite the significant proportions of mild to severe depressive symptoms identified, there was no statistically significant difference in prevalence based on gender.